Combination of a Latency-Reversing Agent With a Smac Mimetic Minimizes Secondary HIV-1 Infection in vitro - Hattori, Shin-ichiro; Matsuda, Kouki; Tsuchiya, Kiyoto; Gatanaga, Hiroyuki; Oka, Shinichi; Yoshimura, Kazuhisa; Mitsuya, Hiroaki; Maeda, Kenji (Frontiers in Microbiology, 2018)
Latency-reversing agents (LRAs) are considered as a potential tool to cure HIV-1, but when taken alone virus production by reactivated cells and subsequent infection will occur. Hence, it is crucial to simultaneously take measures to prevent such secondary HIV-1 infection. In this regard, a strategy to minimize the production of infectious viruses from LRA-reactivated cells is worth pursuing. Here, we focused on an Smac mimetic, birinapant, to induce apoptosis in latently HIV-1-infected cells. When birinapant was administered alone, it only slightly increased caspase-3 expression. However, in combination with an LRA (e.g. PEP005), it strongly induced caspase-3 expression followed by enhanced apoptosis. Importantly, the combination eliminated reactivated cells and drastically reduced HIV-1 production. Finally, we found that birinapant decreased HIV-1 mRNA expression induced by PEP005 in the primary CD4+ T cells from HIV-1-carring patients as well. These results suggest that the combination of an LRA and an "apoptosis-inducing" agent, such as an Smac mimetic, is a possible treatment option to decrease HIV-1 reservoirs without the occurrence of HIV-1 production by reactivated cells.